Application of Flexible Sheet in the Construction of Bio-Battery through Using Immobilized Bacteriorhodopsin - Keshavarz, Enayatollah; Molaeirad, Ahmad (Archives of Advances in Biosciences, 2019)
Introduction: Biophotovoltaic cells have often been studied due to their properties and their potential applications in micro and nano equipments. In order to enhance the quality and versatility of these bio-photocells, flexible sheets such as polyethylene terephthalate (PET) have been widely used. In this study, ZnO nanoporous films were used for immobilization of bacteriorhodopsin (bR) due to the it’s great surface area, measured against titanium dioxide (15TiO2 ). In addition to good conductivity, its superiority was proved by the arrangement of zinc oxide atoms at a suitable temperature. Materials and Methods: In the present study, bacteriorhodopsin was immobilized on ZnO-PET surface through modifying the PET as a photoanode in (Dye-Sensitive Solar Cell) DSSCs. Furthermore, a non-toxicity protein, bR, was substituted for sensitizing ZnO–PET nanoparticles in DSSCs instead of the common expensive chemical-based dyes such as ruthenium-based or organic dyes. Atomic Force Microscopy technique was used to study the morphology of modified PET-ZnO & PET- 15TiO2 surfaces before and after immobilization of bR. Results: AFM images show Signs of excellence in zinc oxide in the atomic arrangement. Finally, the typical I–V curves of the biomolecule-sensitized biosolar cell were obtained. The results indicated that the overall conversion efficiency of the photocell is about 0.16%, a solar cell flux (Jsc) of 0.45 mA cm−2, an open-circuit voltage (VOC) of 0.57 V, and a fill factor of 0.62. Conclusion: Atomic composition of nanoparticles of zinc oxide at a suitable temperature is better than titanium dioxide. This makes the cell more efficient in transporting electrons. the efficiency of the cell produced on the PET bed is appropriate but requires more scientific research.